BlackBox: Stories of the future - Neves, Isabel Clara (2019)
Digital is inevitable and irreversible; it marks the present and helps us to envision the future. There is, however, a story to tell: digital culture is as much about the future as it is about the past, and one must recover a historical perspective on the matter. Black Box — Stories of the Future goes back to the first writings on Digital by designers and architects, intersecting those with the most meaningful present-day reflections on the theme.